Clinical and imaging features of pulmonary mixed squamous cell and glandular papilloma: a case report and literature review - Hu, Xianwen; Zhao, Wei; Li, Fangming; Wang, Pan; Cai, Jiong (Frontiers in Medicine, 2024)
Pulmonary mixed squamous cell and glandular papilloma (MSGP) is a rare benign lung tumor with both squamous and glandular epithelial components. Reports on primary lung MSGP are few and the aim of this study is to describe the imaging including computed tomography (CT) and positron emission tomography (PET) findings, histopathological characteristics of a case of MSGP in our hospital. A 53-year-old woman with no smoking history who underwent a chest CT scan revealed a nodule in the upper lobe of the left lung.The solid nodule showed no lobulation or spiculation but demonstrated significant enhancement on contrast-enhanced CT and increased fluorine-18 fluorodeoxyglucose ( 18 F-FDG) uptake on PET. Moreover, a literature review identified 19 cases of lung MSGP involving imaging findings including CT or/and PET imaging. Except for one patient with ground glass nodule, the rest were solid, and ranged in size from 0.7 to 8.2 cm, which can present as a mildly to significantly increased 18 F-FDG uptake on PET. MSGP is a rare benign tumor entity, and understanding its imaging findings and pathological immunohistochemical 2 characteristics will help to improve the accurate diagnosis of MSGP, so as to avoid unnecessary lobectomy and mediastinal lymph node dissection.